PERAN WALI SANGA DALAM KHASANAH KESUSASTRAAN JAWA - Imam Sutardjo (JURNAL IKADBUDI, 2013)
Javanese literary work creation and product from “Wali Sanga” in the spread of Islam in Java in form of literary works: “suluk, pewayangan, tembang macapat, and lagu dolanan”. If  those four types of literary works aer studied, it will be very benefit and valued in giving various virtue of life teaching.  Human life to be quality, to be the prime man, have a good character,  supreme, wikan sangkan paran, ‘understand the form and the purpose of human return’, and also in the searching of life excelently. Those Wali Sanga literary work also can add wealth and repertoire of valuable Javanese literature development. Various teaching which packed in those marks, need to be revealed to be exemplified and applicated in daily life like hidden pearl and also the sea of Javanese literature value’s wealth which contains of Islamic philosophy.    Keywords: Javanese literature, product, wali sanga, development, primacy of life